PENGARUH EKSTRAK BAWANG HITAM TERHADAP PENURUNAN KADAR GLUKOSA DARAH PADA MENCIT - Pipit Festi W (Universitas Muhammadiyah Surabaya, 2021)
Administration of oral hypoglycemic drugs and insulin is one of the most common pharmacological treatments given to people with diabetes mellitus. This treatment is carried out in the long term so that it causes side effects and is carried out continuously so that it will affect the financial condition of the diabetes mellitus patient. The purpose of this study was to determine the effect of black garlic extract on decreasing blood glucose levels in mice (mus musculus). This study uses the design of True Experimental design (pretest-posttest with control group design). The population is mice in Pusvetma Surabaya. Sampling method uses Non Probability Sampling Purposive Sampling type. Samples taken were 30 mice consisting of 15 intervention groups and 15 control groups. Data was collected using observation sheets, then analyzed using Independent sample t test and Dependent sample t test with a significance level of 5 0.05. The results showed: Using the test Independent sample T test obtained a significance value ρ = 0,000 It can be concluded that there is an effect of black onion extract to reduce blood glucose levels in mice. In the paired t-test test in the treatment group showed ρ = 0,000 that there were differences in blood glucose levels before being given extracts of garlic and after being given intervention. It is expected that black garlic can be used as an alternative medicine to reduce blood glucose levels.Keyword : Ekstrak of black garlic, Blood sugar levels, mus musculus